Determination of Procyanidins by High Performance Liquid Chromatography and Ultraviolet Spectrophotometer - Huo, Qing; Xu, Lei; Kong, Xiangye; Shi, Rongjian (Asian Journal of Chemistry, 2015)
Proanthocyanidins are a mixture of poly polyphenols widespread in nature, in this experiment we establish a quantitative method for the determination of procyanidins, so as to provide references for its development and utilization. The contents of procyanidins is determined by HPLC and HPLC conditions are as follows: A diamonsil C18 column as separation column (250 × 4.6 mm i.d.,10 μm), mobile phase of methanol -0.4 % phosphoric acid (v:v = 1:1), flow rate of 1 mL/min, detection wavelength of 280 nm and column temperature of 30 °C, retention time is 2.55-2.78 min, HPLC standard curve: y = 142773x + 14416, R2 = 0.9998, the linear relationship between the concentration of procyanidins and peak area are good in the range of 20-100 μg/mL, the recovery rates of the procyanidins is 104.83 % with RSD of 1.87 %, the detection limit is 1.25 μg/mL. The contents of procyanidins are determined by UV-spectrophotometer and UV conditions are as follows: ethanol as a constant volume solvent, the absorbance of procyanidins is measured at 471.5 nm. Determination of procyanidins standard curve is A = 0.7438 × C-0.0026, R2 = 0.9997, linear range is 0.014-0.056 mg/mL.